Making a killing : a novel - Hunter, Cara (Hunter, Cara. DI Adam Fawley thriller., 2025)
When Nick Vincent, producer of true-crime show Infamous, hears about an explosive new angle on a high-profile case--the 2016 murder of an eight-year-old girl in Oxford--he leaps at the chance to send a researcher to verify the claims. Two months later, a dog walker discovers a woman's body, bound and buried in a shallow grave in the woods. Forensic evidence links the corpse to the disappearance of that same child. DCI Adam Fawley, the original investigating officer, is called in to run the enquiry. And he remembers the case well--he arrested the child's mother for murder. A murder he now knows she didn't commit. The investigation raises more questions than answers. What connects the two crimes? Where has the dead girl been all these years? How did she manage to disappear? For Adam Fawley, this is personal.